Unconscious Mind and Anxiety in the Main Character of Face in the Crowd Movie Script by Julian Magnad - Dewi Saktiyah Al Khoiriyah (Linguistic, English Education and Art (LEEA) Journal, 2019)
The objectives of the researcher is to describe Unconscious Mind and Anxiety, this research mainly aimed to answer, ‘How is the anxiety reflected in Face in the Crowd movie script?’ , ‘How do the anxieties lead to fantasy in Face in the Crowd movie script?’. Those two problems are analyzed with Psychological of literature or Psychoanalytical approach. The researcher used a qualitative descriptive method in classifying and analyzing the data,the data was taken from movie script entitled Face In the crowd by Julian Magnat. Then, the result of analysis is the description of unconscious mind and anxiety in the main character. In this analysis the researcher divided it into two main points, such as the anxiety in Face in the Crowd movie script, and the anxieties lead to fantasy. Finally, the conclusion from this analysis there are only a few dialogues that show moral anxieties experienced by Anna. And it can be concluded that is the anxiety felt Anna objectivy reality. Anxiety objectivy reality itself is an anxiety that comes from the fear of the danger in the outside world. Then fantasy does not only occur during sleep but when he appeared conscious but without realizing it. The main character in the film derives satisfaction from fantasies that arise when together with her ​​husband, with the Anna vision abnormalities. And fantasy is a process of daydreaming (dreamy) or imagining action to provide an escafrom reality, with satisfaction the achievements obtained and pleasure that are imaginary or die as a hero who does not sin. Keyword: unconscious mind, anxiety, fantasy, and dream